Game Edukasi Matematika untuk Pembelajaran Materi Perkalian dan Pembagian Siswa SD Kelas 4 - Tyar Berliana Umi Kalsum; Nurgiyatna Nurgiyatna (Jurnal Ilmiah Global Education, 2026)
Learning multiplication and division mathematics for 4th grade elementary school students still faces various challenges, one of which is the limited availability of interactive learning media. This study aims to design and develop a Construct 2-based educational mathematics game as an alternative learning medium that is attractive, easy to use, and suitable for schools with limited technological facilities. The game development process follows the Waterfall model, which includes needs analysis, design, implementation, testing, and evaluation. The developed game includes learning materials, gradual game levels, gamification elements, and an automatic assessment system. Testing was conducted using the Black-Box Testing method, the System Usability Scale (SUS), and pretests and posttests to measure student understanding. The test results showed that all game functions functioned well. The usability evaluation resulted in an average SUS score of 86.65, which is categorized as very good, while the pretest and posttest results showed an increase in students' average score from 67.3 to 82.3. Based on these results, the developed educational mathematics game is considered suitable for use as a supporting medium for mathematics learning in elementary schools.